PANDEMIC COVID-19: DAMPAK TERHADAP KEPATUHAN WAJIB PAJAK - Sulistyowatie, Syska Lady; Amelia, Rizky Windar; Pratomo, Sigit Adhi (Widya Dharma Journal of Business - WIJoB, 2023)
The application of the self-assessment system in Indonesia is very influential on tax revenue, this happens not because taxpayers are not willing to pay their taxes but they do not have knowledge of how to calculate, pay and report their taxes. The Covid-19 pandemic that occurred has affected the economy in Indonesia which has an impact on tax revenues in 2020. This qualitative research analyzes how the impact of the Covid-19 pandemic has on taxpayer compliance. Interviews were conducted on 27 taxpayers who had good knowledge about taxes and the remaining 8 other taxpayers had minimal tax knowledge. The results of the interviews are used as statements as research data. Keywords: Tax religiosity, Tax morale, Tax knowledge, Tax sanctions, and Tax service